2013
DOI: 10.1080/01441647.2013.815665
|View full text |Cite
|
Sign up to set email alerts
|

Travel and Subjective Well-Being: A Focus on Findings, Methods and Future Research Needs

Abstract: Subjectively experienced wellbeing has recently attracted increased attention in transport and mobility studies. However, these studies are still in their infancy and many of the multifarious links between travel behaviour and wellbeing are still under-examined; most studies only focus on one aspect of this link (i.e., travel satisfaction). In this paper we give an overview of studies concerning travel and wellbeing, focusing on results, methods and gaps in present research. We suggest that travel behaviour af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
225
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 412 publications
(236 citation statements)
references
References 94 publications
8
225
1
2
Order By: Relevance
“…Although people who do not like to travel will try to self-select themselves in urban neighbourhoods resulting in shorter distances and more active travel, reducing the negative effects of long-distance car use (such as greenhouse gas emissions and congestion), travel haters experience and evaluate their travel less positive compared to travel lovers, which can negatively affect (i) the performance and satisfaction of activities at the destination of the trip and (ii) overall well-being (Bergstad et al, 2011;De Vos et al, 2013;Ettema et al, 2010). People with a more positive stance towards travel are more satisfied with their trips.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although people who do not like to travel will try to self-select themselves in urban neighbourhoods resulting in shorter distances and more active travel, reducing the negative effects of long-distance car use (such as greenhouse gas emissions and congestion), travel haters experience and evaluate their travel less positive compared to travel lovers, which can negatively affect (i) the performance and satisfaction of activities at the destination of the trip and (ii) overall well-being (Bergstad et al, 2011;De Vos et al, 2013;Ettema et al, 2010). People with a more positive stance towards travel are more satisfied with their trips.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, travel behaviour studies are starting to show more interest in how people experience their travel and how satisfied they are with it (De Vos et al, 2013;Ettema et al, 2010Ettema et al, , 2011. Although these studies indicate that there are substantial differences in the way people experience and evaluate their trip according to varying trip characteristics (e.g., weather conditions, congestion levels) and the chosen travel mode (Abou-Zeid, 2009;De Vos et al, 2015a, 2015bDuarte et al, 2010;Ettema et al, 2011;Friman et al, 2013;Olsson et al, 2013), the link between residential location and travel satisfaction has not been analysed thoroughly.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that active travel generates the highest levels of travel satisfaction, while public transport users' experience is most negative (Abou-Zeid, 2009;De Vos et al, 2015;Duarte et al, 2010;Ettema et al, 2011;Friman et al, 2013;Olsson et al, 2013). Various studies have also indicated that other aspects of travel behaviour are associated with the level of travel satisfaction (De Vos et al, 2013;Ettema et al, 2010). These include trip duration (Ettema et al, 2012; see also Stutzer & Frey, 2008); the activities people perform during a trip ; and the environmental conditions in which travel is undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Well-being and travel satisfaction have recently attracted increased attention in transport-related research (De Vos et al, 2013). Over the past years authors have therefore developed scales to measure how people perceive their travel.…”
Section: Introductionmentioning
confidence: 99%
“…(7) Transport and wellbeing Ettema et al (2010), Olsson, Gärling et al (2011), Jakobsson Bergstad, Gamble (2011), de Vos et al (2013 Based on the concept of well-being as an overarching objective, the potential contribution of mobility is examined.…”
Section: The Travel Experience As An Evolving Research Topicmentioning
confidence: 99%